Quality and Inequality of Education 2010
DOI: 10.1007/978-90-481-3993-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Family Background, School System and Academic Achievement in Germany and in Japan

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), directed by Stefano Bartolini since September 2006, is home to a large post-doctoral programme. Created in 1992, it aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society. The Centre hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This variable ranges from 10 to 60, with 10 being the highest grade. Lörz et al (2016) found that students with a higher final grade at secondary school are more likely to study abroad, and students from higher socioeconomic backgrounds and female students have higher average grades (Meisenberg 2016; Ojima and von Below 2010; Roisch 2003). Third, we include subject major to control for the overrepresentation of female students in humanities and social sciences (Böttcher et al 2016; Di Pietro 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This variable ranges from 10 to 60, with 10 being the highest grade. Lörz et al (2016) found that students with a higher final grade at secondary school are more likely to study abroad, and students from higher socioeconomic backgrounds and female students have higher average grades (Meisenberg 2016; Ojima and von Below 2010; Roisch 2003). Third, we include subject major to control for the overrepresentation of female students in humanities and social sciences (Böttcher et al 2016; Di Pietro 2022).…”
Section: Methodsmentioning
confidence: 99%
“…As recent research indicates, these out-of-school lessons show a positive effect on academic achievement (e.g. Baker, Akiba, LeTendre & Wisemann, 2001;Guill & Bonsen, 2011;Haag, 2001Haag, , 2007Hosenfeld, 2011;Konakayama & Matsui, 2008;Mimizuka, 2007;Ojima & von Below, 2010;Southgate, 2009;Streber, Haag & Götz, 2011;Tomura, Nishimaru & Oda, 2011).…”
Section: Shadow Education and Its Implicationsmentioning
confidence: 99%
“…To increase the model fit of my analysis, further influential variables have to be considered, which determine the access to shadow education. Following Ojima and von Below (2010), students' currently attended type of school is considered as one of the most influential covariates besides ESCS.…”
Section: Shadow Education As a Means To Counteract Social Disadvantages?mentioning
confidence: 99%